THE IMPOSSIBILITY OF HOLDING SUGAR ENERGY SECTOR PLANTS LIABLE FOR ACTS BY PRODUCERS IN FUNCTION OF CORPORATE SUPPLY CONTRACTS IN THE VIEW OF LABOR COURTS - Ronquim Filho, Adhemar; da Silva, José Roberto Reis (Seven Editora, 2025)
The article addresses the issue of the lack of liability of sugarcane mills in relation to the labor obligations of producers contracted to supply sugarcane via corporate contracts, according to the case law of labor courts. The research details how the liability of mills is treated in labor courts, especially in contexts in which the production chain involves multiple actors and complex contracts. The article examines court decisions that outline the distinction between the direct liability of mills and the labor obligations of producers, emphasizing that the liability of mills does not automatically extend to the labor debts of contracted producers. In addition, the text explores the legal basis and the interpretation of courts regarding the relationship between mills and producers, considering aspects such as the nature of the contracts, the autonomy of producers, and the absence of a direct employment relationship with the mills. The article concludes that, due to the characteristics of supply contracts and court decisions, mills are not responsible for the labor obligations of producers, emphasizing the importance of understanding the legal implications of these contractual relationships in the sugar-energy sector.DOI: https://doi.org/10.56238/sevened2025.040-009